The Doctor ES's Liability for Filler Injecting Without Full Explanation in Informed Consent Causing Blindness in ADF Left Eye Judging - Dennis Saputra Trikadibusana; Isai Ronny Tanoko; Cynthia Sugandhy; Stefani Berliana Magdalena (IHSA Institute, 2022)
Research titled The Doctor ES's Liability for Filler Injecting Without Full Explanation in Informed Consent Causing Blindness in ADF Left Eye Judging from Act Number 29 of 2004 Regarding Medical Practice and Regulation of the Minister of Health Number 290/MENKES/PER/III/2008 concerning Approval Medical Action discusses the issue of whether the ES doctor is responsible for injecting fillers without a full explanation in the informed consent which causes blindness in the ADF's left eye in terms of Act Number 29 of 2004 Regarding Medical Practice and Regulation of the Minister of Health Number 290/MENKES/PER/III/2008 concerning Approval of Medical Action. The research method used is the statue approach, which means that in answering the main problem through legislation, and using a conceptual problem approach, which means using literature to solve the main problem. The results of the study stated that ES doctors have committed violations of the discipline of the medical profession in the form of not providing a complete explanation to the ADF in seeking approval of medical action or informed consent as referred to in article 3 paragraph (2) letter h of Regulation of the Medical Council No. 4 of 2011 on Professional Discipline of Doctors and Dentists. In addition, ES and ADF doctors as patients have been bound in therapeutic transactions and there are losses suffered by the ADF in the form of permanent blindness in the left eye of the ADF due to the actions of ice doctors, then ES Doctors can also be sued on the basis of default in accordance with Article 1239 of the Civil Code.